(untitled) (Journal of Enam Medical College, 2018)
Dapsone, diamino-diphenyl sulfone, is an antibacterial and anti-inflammatory drug which is used worldwide for treating many diseases, such as leprosy, dermatitis herpetiformis, linear IgA bullous dermatosis, chronic bullous dermatosis of childhood, bullous eruption of systemic lupus erythematosus, erythema elevatum diutinum, leukocytoclastic vasculitis, polyarteritis nodosa and other kinds of vasculitis, prurigo nodularis, nodulocystic acne, cutaneous mycetoma, pustular psoriasis, malaria, pneumocystis carinii pneumonia etc. Since it is widely used, the adverse effects of this drug attract the attention of doctors from different specialities. Dapsone can cause several adverse effects, the most serious one is idiosyncratic systemic hypersensitivity syndrome, namely dapsone hypersensitivity syndrome (DHS), which is potentially fatal, characterized by fever, facial edema with infiltrated papules, generalized papulopustular or exanthematous rash which may extend to exfoliative dermatitis, eosinophilia, lymphadenopathy, hematologic involvement and organ involvement such as hepatitis, nephritis, pneumonitis, encephalitis, myocarditis occurring after 3–6 weeks of drug therapy. Here we have described a case of dapsone hypersensitivity syndrome developed after dapsone therapy for prurigo nodularis. The case is being reported to emphasize the need for timely diagnosis and prompt treatment of this rare complication for successful outcomes. Physicians should be aware of this infrequent but potentially fatal severe form of adverse reaction that can mimic other conditions. J Enam Med Col 2018; 8(2): 108-113